The Relationship Between Knowledge of Mother and Family Support with Immunization Status Td in Sub PIN Difteri - Fajriyah, Ishmatul (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTThe number cases of diphtheria in East Java have increased more years. Surabaya is one of cities that implemented the Sub Pekan Imunisasi Nasional (PIN) Diphtheria. Sub PIN Diphtheria is a program that aims to break the chain of diphtheria transmission. Children aged > 7â15 years are one of the programâs targets Sub PIN Diphtheria. Sub PIN coverage for groups of children aged > 7â15 years in Kalijudan Public Health Center (PHC) only 79.15%, while the predetermined minimum target is 95%. This study was conducted to determine the relationship between knowledge and support from family with immunization status Td in Sub PIN diphtheriae. The research used case kontrol design by using a quantitative approach. The population case is all children aged > 7â15 years in Kalijudan PHC the immunization status Td in Sub PIN program is incomplete. Number of respondents by 60 people. The selection of the sample with simple random sampling. The variabels studied were the characteristics, knowledge, and family support. The results showed that there is a relationship between the level of knowledge of mothers (p = 0.038). There is a relationship between support from family with immunization status Td in sub PIN diphtheria (p = 0.030). It is expected that cross-sector cooperation in the implementation of sub PIN diphtheria and increase knowledge related maternal sub PIN diphtheria and diphtheria by counseling.Keywords: family support, immunization, knowledge, Sub PIN diphtheria